Effect of eicosapentaenoic acid on prevention of lean body mass depletion in patients with exacerbation of chronic obstructive pulmonary disease: A prospective randomized controlled trial. (December 2018) - Ogasawara, Takashi; Marui, Shiori; Miura, Eriko; Sugiura, Masayuki; Matsuyama, Wataru; Aoshima, Yoichiro; Kasamatsu, Norio; Ogiku, Masahito; Ikematsu, Yoshito
Summary: Background & aims: Systemic inflammation plays an important role in the pathogenesis of chronic obstructive pulmonary disease (COPD), resulting in depletion of lean body mass (LBM) and muscle mass. Both frequent exacerbation of COPD and low LBM are associated with poor prognosis. This study aimed to evaluate whether supplementation of eicosapentaenoic acid (EPA) prevents depletion of LBM and muscle mass in hospitalized patients with exacerbation of COPD. Methods: This was a prospective randomized controlled trial, conducted between November 2014 and October 2017. Fifty patients were randomly assigned to receive 1 g/day of EPA-enriched oral nutrition supplementation (ONS) (EPA group) or EPA-free ONS of similar energy (control group) during hospitalization. The LBM index (LBMI) and the skeletal muscle mass index (SMI) were measured using a bioelectrical impedance analyzer at the time of admission and at the time of discharge. Patients underwent pulmonary rehabilitation and wore a pedometer to measure step counts and physical activity. Results: Forty-five patients that completed the experiment were analyzed. Baseline characteristics were similar between the EPA (n = 24) and control groups (n = 21). There were no significant differences in energy intake, step counts, physical activity, or length of hospitalization between the two groups. Although the plasma levels of EPA significantly increased only in the EPA group, we found an insignificant increase in LBMI and SMI in the EPA group compared with the control group (LBMI: +0.35 vs. +0.19 kg/m 2, P = 0.60, and SMI: +0.2 vs. −0.3 kg/m 2, P = 0.17, respectively). The changes in SMI were significantly correlated with the length of hospitalization in the EPA group, but not in the control group (r = 0.53, P = 0.008, and r =−0.32, P = 0.31, respectively) (Fig. 3). Conclusions: EPA-enriched ONS in patients with exacerbation of COPD during short-time hospitalization had no significant advantage in preservation of LBM and muscle mass compared with EPA-free ONS. EPA supplementation for a longer duration might play an important role in the recovery of skeletal muscle mass after exacerbation of COPD.